Hang Tuah : wira Melayu - Mohd. Yusoff Haji Hashim, Datuk Wira; Institut Kefahaman Islam Malaysia (Batu Berendam, Melaka : Institut Kajian Sejarah dan Patriotisme Malaysia, 2008)
The legend of Hang Tuah, a Malay warrior in the court of the Malacca Sultanate.
Includes bibliographical references.
In Malay.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Hang Tuah; Heroes -- Malaysia -- Melaka; Legends -- Malaysia -- Melaka; Legends, Malay; Melaka (Sultanate) -- History